The Role of SPECT/CT in Peritoneal Scintigraphy in the Era of Low-Dose Imaging: A Case Report - Newallo, Domnique S.; Chataigne, Michara; Muzahir, Saima (World Journal of Nuclear Medicine, 2022)
Peritoneal scintigraphy, although rarely used, plays a vital role in the diagnosis of peritoneal dialysis catheter complications. Reported complications include spontaneous hydrothorax secondary to a pleuroperitoneal fistula, which requires the abandonment of peritoneal dialysis, given that a delay in diagnosis can lead to worsening clinical status. Previously reported peritoneal scintigraphy protocols recommended intraperitoneal instillation of radiotracer and moderate-to-large volumes of dialysate or sterile saline ranging from 350 to 2,000 mL. However, smaller volumes, in conjunction with the use of single-photon emission computed tomography/computed tomography, are not verified in patients receiving peritoneal scintigraphy imaging.
Keywords: peritoneal scintigraphy; SPECT/CT; pleuroperitoneal fistula; diaphragmatic defect; peritoneal dialysis catheter